Power and politeness social interaction in Philippine higher education classrooms - Victoria, Mabelle P. (Philippine Journal of Linguistics, 2009)
Drawing upon naturalistic data from Philippine higher education classrooms, this article exmines how talk is used by three Filipino professors to negotiate unequal power relationships and minimize status distinctions between themselves and the students. It uses Brown & Levinson's (1987) politeness theory to unpack how they deploy linguistic resources to soften the exercise of power, create solidarity and mitigate potentially face-threatening acts such as correcting students' errors and giving orders. Data suggest that the professors do not use their institutionally vested power with a blunt force. They employ a mixture of linguistic strategies to subvert the distancing effects of the teacher-student power differential. They emphasise asymmetry to ensure that the objectives of the lesson are met; at the same time they show consideration for the protection and preservation of their students' public self image. This article discusses the complex interface between power and politeness within the context of higher education discourse.